Flucytosine Pharmacokinetics in a Critically Ill Patient Receiving Continuous Renal Replacement Therapy - Kunka, Megan E. (Case Rep Crit Care, 2015)
Purpose. A case report evaluating flucytosine dosing in a critically ill patient receiving continuous renal replacement therapy. Summary. This case report outlines an 81-year-old male who was receiving continuous venovenous hemofiltration (CVVH) for acute renal failure and was being treated with flucytosine for the treatment of disseminated Cryptococcus neoformans infection. Due to patient specific factors, flucytosine was empirically dose adjusted approximately 50% lower than intermittent hemodialysis (iHD) recommendations and approximately 33% lower than CRRT recommendations. Peak and trough levels were obtained, which were supratherapeutic, and pharmacokinetic parameters were calculated. The patient experienced thrombocytopenia, likely due to elevated flucytosine levels, and flucytosine was ultimately discontinued. Conclusion. Despite conservative flucytosine dosing for a patient receiving CVVH, peak and trough serum flucytosine levels were supratherapeutic (120 μg/mL at 2 hours and 81 μg/mL at 11.5 hours), which increased drug-related adverse effects. The results indicate that this conservative dosing regimen utilizing the patient's actual body weight was too aggressive. This case report provides insight into flucytosine dosing in CVVH, a topic that has not been investigated previously. Further pharmacokinetic studies of flucytosine dosing in critically ill patients receiving CVVH are needed in order to optimize pharmacokinetic and pharmacodynamic parameters while avoiding toxic flucytosine exposure.